Design of Temperature Monitoring Equipment for Furnaces Burning Charcoal Production - Setiawan, Arif; Suryapranatha, Dicky; Syifau, Yuni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Charcoal is generally a porous solid material made from carbon with a high degree of aromatization, the result of thermal decomposition of plant waste biomass in conditions without oxygen or with limited oxygen. This traditional method of making charcoal produces charcoal quality that is not optimal and requires constant supervision during the production process. Traditional furnaces or kitchens use soil as an insulator to retain heat during the carbonization process and prevent air from entering the furnace. Optimal combustion can be achieved if several factors in the operation of the furnace are taken into account, including temperature, duration of burning or carbonization, the process of reducing or closing the door, the process of closing the chimney, and the top window. This research aims to design a prototype temperature monitoring system for charcoal burning stoves based on the Arduino Uno microcontroller. This tool will help the operator to know the combustion temperature and completion time of the combustion process, so that the charcoal burning stove is more modern and efficient and can increase the productivity of charcoal making. This system is able to monitor temperatures in real-time and provide important information in handling production time problems. succeeded in increasing production time efficiency. Before using this monitoring tool, operators assumed the charcoal production process time was 12 days. However, after using this monitoring tool, it was discovered that the charcoal production process only took 10 to 11 days. In this way, there is a time saving of 1 to 2 days.Keywords: Charcoal, Burning Furnace, Production Time, Efficiency